Application of antisense oligonucleotide drugs in amyotrophic lateral sclerosis and Huntington’s disease - Kaili Ou; Qingqing Jia; Dandan Li; Shihua Li; Xiao-Jiang Li; Peng Yin (Translational Neurodegeneration)
Abstract Amyotrophic lateral sclerosis (ALS) and Huntington’s disease (HD) are diverse in clinical presentation and are caused by complex and multiple factors, including genetic mutations and environmental factors. Numerous therapeutic approaches have been developed based on the genetic causes and potential mechanisms of ALS and HD. Currently, available treatments for various neurodegenerative diseases can alleviate symptoms but do not provide a definitive cure. Gene therapy, which aims to modify or express specific proteins for neuroprotection or correction, is considered a powerful tool in managing neurodegenerative conditions. To date, antisense oligonucleotide (ASO) drugs targeting the pathological genes associated with ALS and HD have shown promising results in numerous animal studies and several clinical trials. This review provides a comprehensive overview of the development, mechanisms of action, limitations, and clinical applications of ASO drugs in neurodegenerative diseases, with a specific focus on ALS and HD therapeutic strategies.